Proliferative verrucous leukoplakia; a critical appraisal of the diagnostic criteria - Carrard, Vinicius C. (Medicina Oral S.L., 2013)
Since its introduction in the literature in 1985, the term proliferative verrucous leukoplakia (PVL) has been the subject of an ongoing discussion with regard to its definition. Widespread or multifocal occurrence of oral leukoplakia is not just synonymous to PVL. In the present treatise the proposal is made to require the involvement of more than two oral oral subsites, a total added seizeof the leukoplakic areas of at least 3 centimeters, and a well documented period of at least five years of disease evolution being characterized by spreading and the occurrence of one or more recurrences in a previously treated area. Key words:Oral premalignant lesions, leukoplakia, verrucous leukoplakia.